Kewenangan Menteri Keuangan Memilih Ketua Dan Wail Ketua Pengadilan Pajak Berdasarkan Undang-Undang No.14. Tahun 2002: The Authority of the Minister of Finance to Select the Chairman and Deputy Chairman of the Tax Court Based on Law No. 14 of 2002 - Prima Difa Warasaputra; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2024)
In the judicial system, the principle of independence must be upheld to ensure justice. However, there are indications that the autonomy of the tax court is being influenced. This is based on Article 8, paragraph (2) of Law Number 14 of 2002 on the Tax Court, which mandates the proposal of candidates for the positions of Chairman and Deputy Chairman of the Tax Court by the Minister of Finance. Ultimately, the Constitutional Court issued Decision No. 10/PUU-XVIII/2020 as a manifestation of judicial independence. The problem is how the authority of the Minister of Finance in selecting the Chairman and Deputy Chairman of the Tax Court before the Constitutional Court Decision No.10/PUU-XVII/2020, and what are the legal implications of this authority after the Constitutional Court Decision No.10/PUU-XVII/2020. This research is normative juridical in nature. The research is descriptive. Based on the research findings, the Ministry of Finance has the responsibility to guide the organization in both administration and finance of the tax court. Prior to the Constitutional Court's decision, the authority granted to the finance minister was not in line with the independence of the judiciary